A Bibliometric Analysis of Human Resource Management in the Era of Hybrid Work within the Context of Global Digital Transformation - Asriani, Asriani; Syamsiah, Syamsiah (LPPPIPublishing, 2025)
This study conducts a bibliometric analysis of Human Resource Management (HRM) in the era of hybrid work within the context of global digital transformation. The shift toward hybrid work arrangements, accelerated by rapid technological advancement and post-pandemic organizational restructuring, has redefined HRM practices across sectors. Using data retrieved from the Google scholar and Crossref database, this research employs bibliometric mapping and visualization techniques through VOSviewer to identify key trends, influential authors, institutions, and thematic clusters in the literature from 2015 to 2025. The results reveal a growing focus on digital leadership, employee engagement, work life balance, and technological adaptability as central themes. Furthermore, the network visualization highlights collaboration patterns among global researchers, while overlay and density visualizations illustrate the evolution of research topics over time. This study contributes to a deeper understanding of how HRM research adapts to hybrid work models and offers insights for scholars and practitioners in developing sustainable human resource strategies in the digital era.